Penerapan Metode Bernyanyi Untuk Meningkatkan Hasil Belajar Bahasa Arab - Siska; M Wisnu Khumaidi; Rima Ajeng Rahmawati (Program Studi Pendidikan Bahasa Arab, 2023)
This research is based on the low results of learning Arabic owned by grade IV SDIT Baitul Jannah Bandar Lampung so that it can improve Arabic learning outcomes. generate a sense of joy and joy in students, and can solidify knowledge in the minds of students. The formulation of the problem in this study is.